2005
DOI: 10.1097/01.ccm.0000186414.86162.03
|View full text |Cite
|
Sign up to set email alerts
|

Levels of endothelial and platelet microparticles and their interactions with leukocytes negatively correlate with organ dysfunction and predict mortality in severe sepsis

Abstract: Our data support the hypothesis that early increased, not decreased, inflammatory response as measured by our markers is associated with improved survival rate. A high negative correlation was found between some of these markers and Sequential Organ Failure Assessment score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 44 publications
9
115
1
3
Order By: Relevance
“…65,66 The recent availability of diagnostics capable of quantifying MVs of a specific cell origin could be useful for understanding the cells/organs where injury is occurring. This approach will overlap what has been done in oncology.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…65,66 The recent availability of diagnostics capable of quantifying MVs of a specific cell origin could be useful for understanding the cells/organs where injury is occurring. This approach will overlap what has been done in oncology.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…When activated or during apoptosis, these cells can release plasma membrane vesicles called microparticles (MPs) (Martínez et al, 2005). Several studies have shown that in inflammatory diseases, such as diabetes (Sabatier et al, 2002), acute coronary syndromes (Mallat et al, 2000;Bernal-Mizrachi et al, 2003), preeclampsia (Meziani et al, 2006), or sepsis (Soriano et al, 2005), the enhanced level of circulating MPs is correlated with vascular dysfunction, suggesting that MPs might play a role in these pathologies. These data are reinforced by the in vitro studies showing that MPs generated from leukocytes induce cytokine release by endothelial cells Altieri, 1998, 1999).…”
mentioning
confidence: 99%
“…Other authors reported increased level of PMP in septic patients [Nieuwland et al, 2000, Mostefai et al, 2008]. Suprisingly, early elevated level of PMP and endothelial MP may predict a more favorable outcome in severe sepsis [Soriano et al, 2005].…”
Section: Inflammatory Diseasesmentioning
confidence: 97%